2014
DOI: 10.15274/inr-2014-10053
|View full text |Cite
|
Sign up to set email alerts
|

Double-Balloon Remodeling for Coil Embolization of a Primitive Trigeminal Artery Variant Aneurysm

Abstract: Here we describe the case of a patient with a wide-necked unruptured aneurysm arising at origin of a persistent primitive trigeminal artery (PTA) variant from the right internal carotid artery (ICA), supplying the territory of the right superior cerebellar artery and the anterior inferior cerebellar artery. To preserve the ICA and the PTA variant, coil embolization of the aneurysm was performed using a double-balloon remodeling technique (HyperForm™ and Hyper-Glide™ Occlusion Balloon Systems; ev3 Endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Seven cases of cerebral aneurysm complicating PTAv have been reported to date, 5 , 7 12) with surgical treatment performed in two cases 8 , 11) and endovascular treatment in five cases. 5 , 7 , 9 , 10 , 12) Hanabusa et al treated ruptured cerebral aneurysms associated with distal PTAv by embolizing the main trunk of the PTAv proximal to the aneurysm 7) but Yang et al treated a spindle-shaped ruptured aneurysm associated with a proximal PTAv by embolizing the cerebral aneurysm and the PTAv proximal to the aneurysm. 12) In this case, the PTAv was perfusing the right AICA region but analysis of the right SCA and PICA revealed that the PTAv was perfusing the same region in a complementary style, leading to parent artery occlusion with no ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Seven cases of cerebral aneurysm complicating PTAv have been reported to date, 5 , 7 12) with surgical treatment performed in two cases 8 , 11) and endovascular treatment in five cases. 5 , 7 , 9 , 10 , 12) Hanabusa et al treated ruptured cerebral aneurysms associated with distal PTAv by embolizing the main trunk of the PTAv proximal to the aneurysm 7) but Yang et al treated a spindle-shaped ruptured aneurysm associated with a proximal PTAv by embolizing the cerebral aneurysm and the PTAv proximal to the aneurysm. 12) In this case, the PTAv was perfusing the right AICA region but analysis of the right SCA and PICA revealed that the PTAv was perfusing the same region in a complementary style, leading to parent artery occlusion with no ischemic complications.…”
Section: Discussionmentioning
confidence: 99%
“…EVT is a good option for treating these ruptured or symptomatic aneurysms, including reconstructive or deconstructive techniques. Selective coiling with or without balloon/stent assistance can be used to reconstruct PPTA with bifurcation aneurysm or saccular dissection ( Figure 4 ) ( 31 , 34 ).…”
Section: Role Of the Ppta In Aneurysmsmentioning
confidence: 99%
“… 1 , 2 The advances in neuroimaging techniques have led to the increased detection of PPTA and prompted considerable research interest in its clinical significance. 3 , 4 Studies have shown that in approximately 25% of the cases, PPTA occurs in combination with other cerebrovascular lesions, such as aneurysms, 5 cavernous fistula, and arteriovenous malformation, 6 , 7 which are clinically manifested as trigeminal neuralgia, paralysis of the oculomotor nerve or abducens nerve, or palsy of the trochlear nerve. 2 These conditions can lead to compression of the brain stem and, eventually, cerebral ischemia.…”
mentioning
confidence: 99%